A relative value trading system based on a correlation and rough set analysis for the foreign exchange futures market. (May 2017) - Lee, Sukjun; Enke, David; Kim, Youngmin
Abstract: This paper describes the conceptual framework of a relative value (RV)-based trading system focused on the data characteristics of the foreign exchange futures market using a correlation and rough set analysis. RV trading is an investment strategy that can generate potential profits based on the RV of two securities, regardless of market direction. We select pairs with a positive correlation, negative correlation, or no correlation based on the correlation coefficients between foreign exchange futures contracts. To implement and experiment with the proposed system, trading rules are generated using a rough set analysis that employs technical indicators derived from the RVs of the pairs. The performance of the proposed trading system is analyzed using the momentum and buy-and-hold trading strategies as benchmarks. The experimental results and analyses demonstrate that the level of the correlation of the pairs must be considered when developing stable and profitable RV trading systems in a foreign exchange futures market. Highlights: This study proposes a conceptual framework for a relative value trading system. The proposed trading system employs a correlation analysis to form pairs. A rough set analysis is utilized to generate trading rules. Application to the foreign exchange futures market is used to validate the proposed system.